The Role of Management Accounting Information Systems in Mediating Organizational Culture on Managerial Performance in Company X Notary of Bandung City - Johannes Triestanto; Gun Gunawan Rachman; Uswatun Hasanah (Publikasi Indonesia, 2026)
Managerial performance refers to the level of success achieved by managers or individuals within an organization in performing managerial functions, responsibilities, and tasks through planning, organizing, controlling, supervising, and decision-making activities to achieve organizational goals effectively and efficiently. This study aims to examine the effect of organizational culture on managerial performance with a management accounting information system as an intervening variable. The research employed a quantitative method with a descriptive and verification approach. The data sources consisted of primary and secondary data. Data were collected through interviews, questionnaires, and observations involving a population of selected respondents comprising accounting and finance staff from several notary offices of Company X in Bandung City, totaling 90 individuals. The sampling technique used was non-probability sampling with a saturated or census sampling approach. The analytical tools applied in this study included SPSS 25 for descriptive analysis and SmartPLS 3 for verification analysis. The measurement model (outer model) was evaluated through convergent validity, discriminant validity, Average Variance Extracted (AVE), composite reliability, and Cronbach’s alpha. The structural model (inner model) was assessed using the coefficient of determination (R²), f-square, and predictive relevance (Q²). The results of this study indicate that organizational culture influences management accounting information systems, management accounting information systems influence managerial performance, and organizational culture influences managerial performance, with management accounting information systems serving as an intervening variable.